Can you have both fish and bear’s paw? The impact of national innovative city pilot policy on the urban–rural income gap - Zhang, Jiaqing; Zhao, Xindong; Zhao, Dejin (Frontiers in Political Science, 2025)
In advancing China’s high‑quality development, the National Innovative City Pilot Policy has exerted a profound influence on the urban–rural income gap. Based on panel data from 280 prefecture‑level and above cities in China for 2006–2018, this study employs a multi‑period difference‑in‑differences (DID) framework to assess the policy’s impact on urban–rural income gap and its heterogeneous effects, and further investigates the underlying mechanisms through industrial‑structure optimization. The findings indicate that (1) the Pilot Policy significantly widens the urban–rural income gap at the prefecture level and above; (2) It intensifies this disparity via two channels—facilitating industrial upgrading while impeding structural rationalization—with partial mediation contributions of 31.71% and 35.13% of the total effect, respectively. This study concludes with policy recommendations for designing a scientifically grounded innovation system, narrowing income gap, and promoting coordinated urban–rural development.